A new EDC approach for modeling turbulence/chemistry interaction of the gas-phase of biomass combustion. (15th May 2018) - Farokhi, Mohammadreza; Birouk, Madjid
Highlights: A combustion model based on the framework of eddy dissipation concept was proposed. The model is able to describe the chemistry/flow interaction over a wider range of turbulence levels. The model improved the predictions of slow forming and kinetically dominated species. Abstract: Small-scale grate-firing biomass combustors generate high level of pollutants as a result of poor air/fuel mixing and short residence time of combustion. Reliable gas-phase combustion modeling can play a key role in the improvement and optimization of the design of a biomass furnace. This paper proposes a new combustion model based on the framework of the well-known eddy dissipation concept (EDC) approach. The ability of EDC to incorporate detailed chemical reactions in turbulent reacting flows has made it attractive for modeling combustion. However, its application poses a challenge especially for modeling weakly turbulent reacting flow conditions, as well as reacting flows with comparable flow and chemical time scales. The newly proposed combustion scheme can reasonably describe the interaction of chemistry and turbulent flow over a wider range of turbulence conditions. To validate the model, simulations are carried out using diffusion and partially premixed jet flames covering weakly to highly turbulent flow conditions. Moreover, the capability of the new model in predicting NOx emissions, based on fuel bound nitrogen source as well as thermal NOx, is investigated. All numerical results are compared with their counterparts' experimental measurements of temperature and species concentrations. Compared to the standard EDC, the results of the new EDC approach reveal noticeable improvement in the predictions, especially for slow-forming and kinetically dominated species such as CO and NOx .